The Effect of Proanthocyanidin Cocoa Pod Rind Extract (Theobroma cacao L.) on MMP-8 Expession in Gingival Tissue of Periodontitis Rats Model - Yani Corvianindya Rahayu; Agustin Wulan Suci Dharmayanti; Anya Tania Larasati (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
Background: Periodontitis is periodontal tissue inflammation due to Porphyromonas gingivalis which invades the gingival tissue due to the activity of virulence factors. This causes the host immune system changes and increases MMP-8 production in periodontal tissue so resulting excessive tissue destruction. Cocoa pod rind containing proanthocyanidin compound as anti-inflammatory drugs is given to reduce MMP-8 and cure periodontitis. Objective: To examine the effect of proanthocyanidin extract of cocoa pod rind (Theobroma cacao L.) on decreasing MMP-8 expression in gingival tissue of periodontitis rats model. Materials and Methods: The samples used were 16 male Wistar rats divided into 2 groups, placebo gel for the control group and proanthocyanidins gel for the treatment group. ). Each group was induced by P.gingivalis bacteria every 3 days for 14 days and then smeared with placebo gel and proanthocyanidin gel for 7 and 14 days. Then all rats’ gingival tissue were taken and made preparations to be observed under a microscope and analyzed using immunoratio software. Result: There were differences in MMP-8 expression based on observation time (p<0.05). MMP-8 expression in the 7th day control group was lower than the 14th day and MMP-8 expression in the 7th day treatment group was higher than the 14th day. Conclusion: Proanthocyanidin of cocoa pod rind extract (Theobroma cacao L.) can reduce MMP-8 expression in gingival tissue of periodontitis rats model.